2018
DOI: 10.1155/2018/7202985
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Intraurban Land Use Dynamics under Multiple Scenarios Based on Fuzzy Cellular Automata: A Case Study of Jinzhou District, Dalian

Abstract: The spatial evolution of land use in Jinzhou area was simulated using fuzzy cellular automata to determine all factors influencing urban land use change. For this purpose, land use data of multiple sources and remote sensing images from 2003 to 2015 were analyzed. The following results were obtained: (1) real land use data and simulation data for 2015 were tested using four indices. Under the 5 m × 5 m scale, the model shows good performance for simulation of areas with various land use types. (2) Among simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 84 publications
0
31
0
Order By: Relevance
“…It can be found that population density has a more significant correlation with kappa coefficient than population and income (r = −0.269, p = 0.2812). [22,45,[55][56][57]. Especially, socio-economic data have a confirmatory impact to the simulation of the CA-Markov model [58].…”
Section: Relationship Between Kappa Coefficient and Landscape Populamentioning
confidence: 88%
See 3 more Smart Citations
“…It can be found that population density has a more significant correlation with kappa coefficient than population and income (r = −0.269, p = 0.2812). [22,45,[55][56][57]. Especially, socio-economic data have a confirmatory impact to the simulation of the CA-Markov model [58].…”
Section: Relationship Between Kappa Coefficient and Landscape Populamentioning
confidence: 88%
“…The greater the population density, the more complicated the land use. The population density is also a significant factor affecting simulation in many studies [22,55,56,59]. Therefore, both population density and kappa coefficient have a correlation that cannot be ignored.…”
Section: Relationship Between Kappa Coefficient and Landscape Populamentioning
confidence: 99%
See 2 more Smart Citations
“…e mechanisms that influence such efficiency are complex and diverse [20]. A number of studies have shown that fiscal expenditure, urban population density [23], transportation infrastructure [9,24,25], and urban industrial composition, and layout [26] have an impact on urban construction land efficiency [27]. However, researchers are yet to reach a consensus in regard to the quantitative measurements and mechanisms of urban construction land use efficiency.…”
Section: Variable Selection and Processingmentioning
confidence: 99%